Decree Establishing that New Automobile and Motorcycle Spare Parts May Be Sold only Turn-In of Old Part - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Item based on interviews conducted with defectors and immigrants in Western refugee camps and immigration offices, or Western travelers returning from stays in East European communist countries, supplemented with information collected through Radio Free Europe (RFE) correspondence with anonymous sources from behind the Iron Curtain. This field report was assigned the following topical and geographical subject headings by the RFE/RL: Hungary; Communications -- Vehicles